TERRITÓRIO E ALIMENTAÇÃO: ESTUDO DE CASO DA COMUNIDADE INDÍGENA DE AREAL E SANTA MARIA – RIO DOCE (LINHARES-ES) - Vargas, André Azoury (2021)
This work addresses the relationship between territory and food, taking as a case study the Botocudo (Borum) and Tupinikim indigenous community of Areal and Santa Maria; located in the region of the mouth of the Doce river, which is in the municipality of Linhares (Espírito Santo – Brazil). The Traditional Peoples and Communities at the mouth of the Doce river suffer from the impacts resulting from the hegemonic process of capitalist development since the colonial period. The environment at the mouth of the Doce river is very fragile as a result of the social and environmental impacts suffered over the years, with emphasis on the deforestation of the native forest (Atlantic Forest); implementation of drainage channels in the coastal plain; oil exploration; and contamination of the Doce river by mining tailings after the collapse of the Fundão dam - belonging to Samarco SA (Vale/ BHP Billiton). From this scenario of conflict and territorial disputes, we sought to analyze the processes of transformation of the traditional way of life and eating habits of the Community of Areal and Santa Maria between the second half of the 20th century and the year 2020. The methodology used involved a review bibliographical and documental, case study and qualitative interviews. The work proceeded theoretically, through geographical concepts: territory, milieu, habitat, gender/ way of life and food complexes, guiding reflections on food, referenced in the classic authors of modern and contemporary Geography, as well as in authors of Sociology, Anthropology and History of Food. From the multidisciplinary and multidimensional reflection on the issue of access to and consumption of food, it was possible to understand the material and symbolic power relations present in the mouth of the Doce river. The results showed that changes in eating habits and the loss of the food sovereignty of the Areal e Santa Maria community are directly linked to the aforementioned impacts and complex processes of a global-local nature.